Analisa Kerentanan Sosial Lingkungan Kota Jakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2008)
lndonesiil is positioned at the third position among the most populated and the highest urbanization countries. This reality results in negative implication, i.e. the increase of social vulnerability of the people in the urban area. The aim of this research is to identify and to criticize the socio-economic and the environmental vulnerability as a consequence of that phenomenon. This article presents sociill vulnerability quantification in DKI Jakarta as a mega-city in lndonesiil by using qualitative analysis. Some researches pointed out that Jakarta is very vulnerable to shock and stress based on the number of population factor, basic infrastructure, economic sustainability condition, social and unavailability of sustainable planning documents. The redemption scenarios are carried out by using two ways, i.e. optimistic and pessimistic scenarios.